Method for sealing side edge of mobile terminal screen by using epoxy adhesive
By using epoxy adhesive on the edge of the mobile terminal screen to disperse into small droplets under the action of an electric field and photocure, the problem of insufficient edge sealing accuracy and bonding strength in the prior art is solved, and high precision, stability and Corrosion-resistant screen edge sealing effect.
Patent Information
- Application Number
- CN202411439384.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to achieve high precision and high stability when sealing the edges of the screen of mobile terminals. In the narrow frame design, the adhesive strength is low when the adhesive layer is thin, making it difficult to resist the erosion of sweat and grease.
Epoxy adhesive is used to disperse into small droplets under the action of an electric field, and spray it at a specific flow rate to the place to be bonded. The dispensing is completed in combination with photocuring technology to ensure the accuracy of the glue line and the bonding strength.
It achieves high-precision and high-stability screen edge sealing, ensuring that the adhesive layer still has good bonding strength when it is thin, and has excellent sweat and grease resistance, extending the service life of the screen.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure FDA0005085950770000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic products, and in particular relates to a method for sealing the side edge of a mobile terminal screen by using an epoxy adhesive. Background Art
[0002] During the assembly process of the mobile terminal, the screen, motherboard, battery, etc. need to be placed in the shell and fixed. There is a gap between the screen and the shell. Generally, glue is needed to fill the gap to achieve screen edge sealing and a firm fit between the screen and the shell. The screen edge of the mobile terminal needs to resist the erosion of sweat and grease that consumers may come into contact with during use for a long time. Taking high-end narrow-framed mobile phones as an example, due to the narrow frame, this erosion effect is more obvious. Over time, the screen will gradually be damaged, thereby affecting its performance and service life. As mentioned above, the prior art already has glue to seal the screen. However, due to the design requirements of the narrow frame, the area that can be used for glue protection is very limited, and high-precision glue protection must be achieved under extremely fine specifications to ensure the long-term stability and reliability of the screen. In addition, due to the design requirements of the narrow frame, the glue layer is required to have good bonding strength even when it is very thin, and it is resistant to erosion by sweat, grease, etc.
[0003] In the edge sealing process of traditional mobile terminals, the glue is usually applied to the edge area of the screen through piezoelectric spray valve technology (by applying voltage to the piezoelectric sheet to cause the piezoelectric sheet to deform, thereby causing changes in fluid pressure) and then solidified to protect the screen. However, the piezoelectric spray valve technology cannot achieve precise control of the glue flow rate and cannot ensure the consistency of the size and shape of the sprayed droplets, which will reduce the accuracy of the glue line, making it impossible to ensure the long-term stability and reliability of the screen. At the same time, the bonding strength is low when the glue layer is thin. Summary of the invention
[0004] The first object of the present invention is to provide a method for gluing using an epoxy adhesive, which can not only achieve high precision and high stability, but also has good bonding strength when the adhesive layer is thin, and has excellent sweat resistance and grease resistance.
[0005] Specifically, the gluing method provided by the present invention comprises dispersing the epoxy adhesive into small droplets under the action of an electric field and spraying the small droplets to the bonding site at a flow rate of 0.5 to 10 mm / s to complete the gluing, wherein the voltage of the electric field acting on the epoxy adhesive is 2200 to 5000 V and the air pressure is 200 to 700 kPa, and then the obtained glued part is photocured; the viscosity of the epoxy adhesive at 25° C. is 5000 to 20000 cps and the thixotropy is 2 to 8, and the epoxy adhesive has a strength of 1000 mJ / cm 2The bonding strength after UV light irradiation is 10 MPa or more.
[0006] The second object of the present invention is to provide a method for sealing the side of a mobile terminal screen, wherein the mobile terminal comprises a screen and a shell, and a gap is provided at the connection between the periphery of the screen and the shell, and the method comprises applying glue to the gap using the above method.
[0007] Piezoelectric spray valve technology is a "squeeze" spray printing. Although the piezoelectric spray valve technology can successfully apply adhesive to the edge of the screen, due to the influence of many factors such as electrical signals, chips, and diaphragms, the glue flow cannot be accurately controlled, and the consistency of the size and shape of the sprayed droplets cannot be ensured, which will lead to a decrease in the accuracy of the glue line, and thus the long-term stability and reliability of the screen cannot be guaranteed. In addition, the piezoelectric spray valve technology seems to be able to achieve "continuous" glue application, but this is only because the glue application time between droplets has been shortened to a "continuous" range that can be judged by the naked eye, that is, "continuous" in appearance, not "continuous" in an absolute sense. When non-continuous droplets are applied to the bonding area (such as the side gap of the mobile terminal screen), the bonding surface cannot be absolutely infiltrated and spread by the adhesive, so high bonding strength cannot be achieved at a thin thickness. When sweat and grease penetrate into the glue layer, it is also easy to erode the glue layer, thereby affecting the performance and service life of the glue application component. The reason why the existing technology chooses piezoelectric spray valve technology is that it is easy to apply glue, can realize automatic control, and has high production efficiency. More importantly, according to traditional thinking, other gluing methods such as electrofluid inkjet printing technology can achieve more precise control, but it has extremely high requirements for adhesives. Improper selection of adhesives will make it difficult to effectively disperse into small droplets during the spraying process, easily form a spray or discontinuous dispensing, and the droplets are easy to flow after spraying, causing blur or diffusion.
[0008] The key to the present invention is to select an epoxy adhesive with specific viscosity and thixotropy and apply the adhesive in a dual coupling manner of air pressure and voltage under the action of an electric field. This can significantly improve the long-term stability and reliability of the screen. When the adhesive layer is thin, it still has good bonding strength and excellent sweat and grease resistance. It is speculated that the reason may be that: the present invention sprays the epoxy adhesive into the gap under the dual effects of air pressure and voltage, and the epoxy adhesive forms a meniscus based on the thrust of air pressure, and pulls the jet out from the top of the meniscus in a "pulling" manner with the help of the electric field, and forms a Taylor cone under the action of the high-voltage electric field, and then forms a micro-nano jet. The specific viscosity and thixotropy of the epoxy adhesive can not only make it effectively dispersed into micro-nano jets and accurately applied to the gap in the form of small droplets, but also ensure the continuous and stable gluing process, so that the size and shape of the sprayed droplets are highly consistent, which can avoid the droplets flowing after the jet and causing blurring or diffusion, ensure the high precision of the glue line specifications, thereby ensuring the long-term stability and reliability of the screen, and at the same time shorten the gluing time between droplets, so that the surface to be bonded can be fully infiltrated and spread by the adhesive, and high bonding strength can be obtained at a thinner thickness, thereby improving the ability to resist sweat and grease corrosion. DETAILED DESCRIPTION
[0009] The gluing method provided by the invention comprises dispersing the epoxy adhesive into small droplets under the action of an electric field and spraying the small droplets to the places to be bonded to complete the gluing, and then light-curing the glued parts.
[0010] In the present invention, the injection flow rate of the epoxy adhesive must be controlled at 0.5 to 10 mm / s. When the injection flow rate is lower than 0.5 mm / s, not only is the process efficiency low, the glue application time is longer, but the glue is also prone to aggregation and collapse; when the injection flow rate is greater than 10 mm / s, extremely high requirements are placed on the adhesive extrusion performance, and it is easy to have uneven glue lines, less glue, and lack of glue. The injection speed can be specifically 0.5, 0.8, 1, 2, 5, 8, 10 mm / s or any value therebetween.
[0011] In the present invention, the viscosity of the epoxy adhesive at 25°C must be controlled within the range of 5000-20000 cps and the thixotropy must be controlled within the range of 2-8. The epoxy adhesive has a strength of 1000 mJ / cm 2The bonding strength after UV light irradiation is above 10MPa. When the viscosity is lower than 5000cps, the adhesive droplets are prone to flow after spraying, resulting in blurring or diffusion, thereby affecting the accuracy of the glue line; when the viscosity is higher than 20000cps, the adhesive is not only difficult to be effectively dispersed into small droplets during the spraying process, but also the droplets formed by the spraying have low consistency in shape. When the thixotropy is lower than 2, the adhesive is prone to collapse and overflow on the product, and it cannot form effective protection. At the same time, it will also affect the performance of other areas (such as the mobile terminal screen display area); when the thixotropy is higher than 8, the adhesive cannot be evenly spread, and there may be a risk that the parts that need protection cannot be completely filled. In the present invention, the epoxy adhesive is evaluated to have a strength of 1000mJ / cm 2 When the bonding strength after UV light irradiation is 1000mJ / cm 2 When the bonding strength after UV light irradiation is lower than 10MPa, the thickness of the final adhesive layer is thin because the range of allowed glue application is very small. When the thickness of the adhesive layer is thin, good bonding strength cannot be obtained, and it cannot be used to seal the side of the screen of a narrow-framed mobile terminal. The viscosity of the epoxy adhesive at 25°C can be 5000, 8000, 10000, 12000, 15000, 18000, 20000cps or any value therebetween. The thixotropy of the epoxy adhesive can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 or any value therebetween. The epoxy adhesive has a strength of 1000mJ / cm 2 The bonding strength after UV light irradiation can specifically be 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa, 20 MPa, 22 MPa, 24 MPa, 26 MPa, 28 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa or any value therebetween.
[0012] In the present invention, the voltage of the electric field acting on the epoxy adhesive is 2200-5000V and the air pressure is 200-700kPa. When the voltage is less than 2200V, the glue outlet has the defects of easy glue aggregation, small glue amount, and poor glue consistency; when the voltage is greater than 5000V, the glue is very easy to disperse and has poor consistency. When the air pressure is less than 200kPa, the glue outlet has the defect of poor or even no glue outlet; when the air pressure is greater than 700kPa, the glue outlet has the defect of easy dispersion and overflow of glue during high-precision dispensing. The voltage can be specifically 2200V, 2500V, 3000V, 3500V, 4000V, 4500V, 5000V or any value therebetween. The air pressure may be 200 kPa, 250 kPa, 300 kPa, 400 kPa, 450 kPa, 500 kPa, 550 kPa, 600 kPa, 650 kPa, 700 kPa or any value therebetween. In the present invention, the air pressure refers to the gauge pressure.
[0013] In a preferred embodiment, the spray distance of the epoxy adhesive to the bonding site is 0.01-0.8 cm, which has the advantages of high-precision adhesive application and precise adhesive control for extremely small bonding requirements. The spray distance can be 0.01 cm, 0.1 cm, 0.15 cm, 0.2 cm, 0.25 cm, 0.3 cm, 0.35 cm, 0.4 cm, 0.45 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, etc.
[0014] In a preferred embodiment, the dispensing thickness of the epoxy adhesive is 0.03-0.5 mm, specifically 0.03 mm, 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm or any value therebetween.
[0015] In a preferred embodiment, the intensity of the light curing is 1000-10000 mJ / cm 2 , for example, it can be 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 mJ / cm 2 or any value in between.
[0016] In a preferred embodiment, the epoxy adhesive contains the following components in parts by weight:
[0017]
[0018] In the present invention, the epoxy resin may be an aliphatic epoxy resin having two or more epoxy groups, an aromatic epoxy resin having two or more epoxy groups, or a mixture of the two. From the perspective of compatibility with thiol compounds, the epoxy resin preferably contains at least an aromatic epoxy resin having two or more epoxy groups compared to the aliphatic epoxy resin having two or more epoxy groups. The mass ratio of the aliphatic epoxy resin having two or more epoxy groups to the aromatic epoxy resin contained in the epoxy resin is preferably ≤1:4.
[0019] In the present invention, the aliphatic epoxy resin having two or more epoxy groups may be at least one of a binary epoxy resin, a ternary epoxy resin, etc. Specific examples of the binary epoxy resin include, but are not limited to, at least one of (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, polytetramethylene ether glycol diglycidyl ether, glycerol diglycidyl ether, neopentyl glycol diglycidyl ether, cyclohexane type diglycidyl ether, and dicyclopentadiene type diglycidyl ether. Specific examples of the ternary epoxy resin include, but are not limited to, trimethylolpropane triglycidyl ether and / or glycerol triglycidyl ether.
[0020] In the present invention, the aliphatic epoxy resin having two or more epoxy groups may be at least one of an alicyclic epoxy resin, a glycidylamine epoxy resin, a hydantoin epoxy resin, an epoxy resin having a siloxane skeleton, and the like. Specific examples of the alicyclic epoxy resin include, but are not limited to, vinyl (3,4-cyclohexene) dioxide and / or 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-dioxane, 2,2-bis(3,3'-epoxycyclohexyl)propane, di-4-epoxycyclohexane, and 3,4-epoxycyclohexyl carboxylate. The glycidylamine epoxy resin may be, for example, tetraglycidylbis(aminomethyl)cyclohexane. The hydantoin epoxy resin may be, for example, 1,3-diglycidyl-5-methyl-5-ethylhydantoin. The epoxy resin having a siloxane skeleton may be, for example, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane.
[0021] In the present invention, the epoxy equivalent of the aliphatic epoxy resin having two or more epoxy groups is preferably 50 to 600 g / eq, such as 50, 80, 100, 200, 300, 400, 500, 600 g / eq or any value therebetween.
[0022] In the present invention, the aromatic epoxy resin having two or more epoxy groups can be various existing epoxy resins with two epoxy groups and containing aromatic ring structures, and specific examples thereof include but are not limited to: bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, tetrabromobisphenol A epoxy resin, fluorene epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin (such as 1,4-phenyl dimethanol diglycidyl ether), biphenyl epoxy resin (such as 3,3',5,5'-tetramethyl-4,4'-diglycidyloxy biphenyl), glycidylamine epoxy resin (such as diglycidyl aniline, diglycidyl toluidine, triglycidyl p-aminophenol, tetraglycidyl meta-xylene diamine, etc.), at least one of the epoxy resins containing naphthalene rings, preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and glycidylamine epoxy resin.
[0023] In the present invention, the epoxy equivalent of the aromatic epoxy resin having two or more epoxy groups is preferably 50 to 600 g / eq, such as 50, 80, 100, 200, 300, 400, 500, 600 g / eq or any value therebetween.
[0024] In addition, the content of the epoxy resin can be specifically 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 parts by weight or any value therebetween.
[0025] In the present invention, the cationic photoinitiator may be a sulfonium salt compound or an iodonium salt compound. Specific examples of the sulfonium salt compound include, but are not limited to, at least one of diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluoroantimonate, diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate, diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluorophosphate and benzyl(4-hydroxyphenyl)methylsulfonium hexafluoroantimonate. Among them, specific examples of the iodonium salt compounds include, but are not limited to: at least one of 4-isopropyl-4'-methyldiphenyl iodide tetrakis(pentafluorophenyl)borate, bis[4-n-alkyl(C10-13)phenyl]iodonium tetrakis(pentafluorophenyl)borate, 4-isobutylphenyl-4'-methylphenyl iodonium hexafluorophosphate and bis(4-dodecylbenzene)iodonium hexafluoroantimonate. In addition, the cationic photoinitiator can be specifically 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween.
[0026] In the present invention, the photosensitizer includes but is not limited to at least one of 2-isopropylthioxanthone, benzil dimethyl ketal, hydroxycyclohexyl phenyl ketone, 2,4-diethylthiazolone, hydroxydimethyl acetophenone, methyl-(4-methylthiophenyl)-2-morpholinyl-acetone, 2,4-diethylthioxanthone, ethyl 4-dimethylaminobenzoate, benzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and methyl benzoylformate. In addition, the photosensitizer can be specifically 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween.
[0027] In the present invention, specific examples of the toughening agent include, but are not limited to: 1,4-butanediol, 1,6-hexanediol, polymethanol, polyethylene glycol, polypropylene glycol, glycerol, trihydroxy polyoxypropylene ether, D-glucose polyethylene oxide, polyoxyethylene polyoxypropylene ether, polymers of methyl ethylene oxide, ethylene oxide and 1,2,3-propanetriol, polymers of methyl ethylene oxide, 1,2-ethylenediamine and ethylene oxide, 1,2-ethylenediamine epoxy At least one of a polymer of propane, a trimethylol propane poly (oxypropylene) triether, a polymer of methyl oxirane and oxirane ethyl ether and a polymer of 2-ethyl-2-hydroxymethyl-1,3-propanediol, a pentaerythritol propoxylate, polytetrahydrofuran diol, 1,1-[1-methylethyl)-bis-4,1-phenyleneoxy]-di-2-propanol, a hydroxy-terminated polybutadiene, polyhexanediol adipate and polyethylene adipate. In addition, the toughening agent can be specifically 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50 parts by weight or any value therebetween.
[0028] In the present invention, specific examples of the silane coupling agent include, but are not limited to, at least one of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane, γ-glycidyloxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, and 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane. In addition, the silane coupling agent may be specifically 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween.
[0029] In the present invention, specific examples of the inorganic filler include, but are not limited to, at least one of silicon dioxide, fumed silica, aluminum oxide, talc, calcium carbonate, barium sulfate, mica, quartz powder, glass powder, aluminum hydroxide, zinc oxide, aluminum nitride, silicon carbide, silicon nitride, boron nitride, titanium nitride, dolomite, titanium dioxide, aluminum silicate, calcium silicate, bentonite, magnesium oxide, magnesium hydroxide, magnesium silicate, cobalt silicate, zirconium oxide, and barium titanate. In addition, the inorganic filler may specifically be 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween.
[0030] In the present invention, specific examples of the toner include, but are not limited to, at least one of carbon black, red iron oxide, black iron oxide, titanium dioxide, brown iron oxide, permanent yellow SD-GTL PY14, and phthalocyanine blue. In addition, the toner may be specifically 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween.
[0031] The present invention also provides a method for sealing the side of a mobile terminal screen, wherein the mobile terminal includes a screen and a shell, and a gap is provided at the connection between the periphery of the screen and the shell, wherein the method includes dispersing the epoxy adhesive into small droplets under the action of an electric field and spraying these small droplets to the gap at a flow rate of 0.5 to 10 mm / s to complete the dispensing, wherein the voltage of the electric field acting on the epoxy adhesive is 2200 to 5000 V and the air pressure is 200 to 700 kPa, and then the obtained dispensing part is photocured to complete the sealing.
[0032] In the present invention, the width of the gap may be, for example, 0.05-2 mm, such as 0.05 mm, 0.08 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm or any value therebetween.
[0033] In the present invention, the mobile terminal may be, for example, a mobile phone, a computer or a car-mounted screen.
[0034] The present invention will be described in detail below through examples.
[0035] In the following preparation examples, comparative preparation examples, embodiments and comparative examples, the parts of raw materials are all parts by weight.
[0036] In the following preparation examples, comparative preparation examples, embodiments and comparative examples, the sources of the raw materials are as follows:
[0037] Epoxy resin (3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate): 2021P, purchased from Daicel Japan, CAS No. 2386-87-0;
[0038] Sulfonium salt cationic photoinitiator (diphenyl[4-(phenylthio)phenyl]-sulfonium hexafluoroantimonate): UVI-6976, purchased from Dow Chemical;
[0039] Photosensitizer (2-isopropylthioxanthone) was purchased from Aladdin;
[0040] Toughener (trimethylolpropane poly(oxypropylene) triether) was purchased from Alfa Chemistry;
[0041] Silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane) was purchased from Momentive;
[0042] Inorganic filler (fumed silica) was purchased from Aladdin;
[0043] Toner (carbon black) was purchased from Alfa Chemistry.
[0044] Preparation Example 1 Preparation of epoxy adhesive
[0045] 60 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 30 parts of toughening agent, 2 parts of silane coupling agent, 4 parts of filler and 2 parts of color powder were mixed to obtain epoxy adhesive, which was recorded as BJ-1. The epoxy adhesive BJ-1 had a viscosity of 16000 cps at 25°C and a thixotropy of 5.
[0046] Preparation Example 2 Preparation of epoxy adhesive
[0047] 65 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 25 parts of toughening agent, 2 parts of silane coupling agent, 3 parts of filler and 2 parts of color powder were mixed to obtain epoxy adhesive, which was recorded as BJ-2. The epoxy adhesive BJ-2 had a viscosity of 10000 cps at 25°C and a thixotropy of 3.5.
[0048] Preparation Example 3 Preparation of epoxy adhesive
[0049] 70 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 20 parts of toughening agent, 2 parts of silane coupling agent, 2 parts of filler, and 1.5 parts of color powder were mixed to obtain epoxy adhesive, which was recorded as BJ-3. The epoxy adhesive BJ-3 had a viscosity of 6000 cps at 25° C. and a thixotropy of 2.5.
[0050] Comparative Preparation Example 1 Preparation of Traditional Adhesive
[0051] 55 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 30 parts of toughening agent, 2 parts of silane coupling agent, 7 parts of filler and 3 parts of color powder were uniformly mixed to obtain a conventional adhesive, which was recorded as DBJ-1. The conventional adhesive DBJ-1 had a viscosity of 30,000 cps at 25° C. and a thixotropy of 10.
[0052] Comparative Preparation Example 2 Preparation of Epoxy Adhesive
[0053] 65 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 25 parts of toughening agent, 2 parts of silane coupling agent, 5 parts of filler, and 2.5 parts of color powder were mixed to obtain a reference epoxy adhesive, which was recorded as DBJ-2. The reference epoxy adhesive DBJ-2 had a viscosity of 25000 cps at 25°C and a thixotropy of 8.5.
[0054] Comparative Preparation Example 3 Preparation of Epoxy Adhesive
[0055] 75 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 15 parts of toughening agent, 2 parts of silane coupling agent, 2.5 parts of filler, and 1.5 parts of color powder were mixed to obtain a reference epoxy adhesive, which was recorded as DBJ-3. The viscosity of the epoxy adhesive DBJ-3 at 25° C. was 3500 cps and the thixotropy was 1.8.
[0056] Comparative Preparation Example 4 Preparation of Epoxy Adhesive
[0057] 75 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 15 parts of toughening agent, 2 parts of silane coupling agent, 1.5 parts of filler and 1 part of color powder were uniformly mixed to obtain a reference epoxy adhesive, which was recorded as DBJ-4. The viscosity of the epoxy adhesive DBJ-4 at 25° C. was 2100 cps and the thixotropy was 1.5.
[0058] Comparative Preparation Example 5 Preparation of Epoxy Adhesive
[0059] 75 parts of epoxy resin, 0.5 parts of cationic photoinitiator, 2 parts of photosensitizer, 15 parts of toughening agent, 2 parts of silane coupling agent, 1 part of filler, and 0.5 parts of color powder were mixed to obtain a reference epoxy adhesive, which was recorded as DBJ-5. The viscosity of the epoxy adhesive DBJ-5 at 25° C. was 1000 cps and the thixotropy was 1.1.
[0060] Embodiment 1 sizing method
[0061] The epoxy adhesive BJ-1 was dispersed into small droplets under the action of an electric field of 5000V (air pressure 500kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto the stainless steel sheet at a speed of 1mm / s to form a glue dot of 0.1mm×0.1mm in area. The spray distance was set at 0.03cm and the glue thickness was controlled at 0.1mm. Then, the tempered glass sheet was overlapped on the glue dot and a 1000mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0062] Embodiment 2 sizing method
[0063] The epoxy adhesive BJ-2 was dispersed into small droplets under the action of an electric field of 3800V (pressure 350kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto the stainless steel sheet at a speed of 2.5mm / s to form a glue spot with an area of 0.2mm×0.2mm. The spray distance was set at 0.07cm and the glue thickness was controlled at 0.1mm. Then, the tempered glass sheet was overlapped on the glue spot and 1000mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0064] Embodiment 3 sizing method
[0065] The epoxy adhesive BJ-3 was dispersed into small droplets under the action of an electric field of 2500V (air pressure 200kPa) using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and sprayed onto the stainless steel sheet at a speed of 5mm / s to form a glue dot with an area of 0.3mm×0.3mm. The spray distance was set at 0.13cm and the glue thickness was controlled at 0.1mm. Then, the tempered glass sheet was overlapped on the glue dot and a 1000mJ / cm 2 The glue point is irradiated with an intensity to complete the curing and obtain a cured part.
[0066] Comparative Example 1 Gluing method
[0067] Glue is applied according to the method of Example 1, except that piezoelectric spray valve technology is adopted and a Vermes piezoelectric spray valve is used for dispensing. Specifically, the equipment dispenses glue according to the following parameters: rise time 1.5msec, fall time 0.1msec, valve opening time 1.0msec, striker stroke 68%, delay 0.1msec, speed 35mm / s, air pressure 0.4MPa, nozzle diameter 0.10mm, and other conditions are the same as in Example 1 to obtain a cured part.
[0068] Comparative Example 2 Gluing Method
[0069] The glue was applied according to the method of Example 1, except that manual glue dispensing was used. The other conditions were the same as those of Example 1, and a cured part was obtained.
[0070] Comparative Example 3 Gluing Method
[0071] The glue was applied according to the method of Example 1, except that a robotic arm was used for glue dispensing. The other conditions were the same as those of Example 1, and a cured part was obtained.
[0072] Comparative Example 4 Gluing Method
[0073] Gluing was performed according to the method of Example 1, except that the glue dispensing flow rate was controlled at 0.2 mm / s. The other conditions were the same as those of Example 1, and a cured part was obtained.
[0074] Comparative Example 5 Gluing Method
[0075] Gluing was performed according to the method of Example 1, except that the glue dispensing flow rate was controlled at 12 mm / s. The other conditions were the same as those of Example 1, and a cured part was obtained.
[0076] Comparative Example 6 Gluing Method
[0077] The gluing was performed according to the method of Example 1, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-1 of the same weight portion, and the other conditions were the same as those of Example 1 to obtain a cured part.
[0078] Comparative Example 7 Gluing Method
[0079] The gluing was performed according to the method of Example 1, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-2 of the same weight portion, and the other conditions were the same as those of Example 1 to obtain a cured part.
[0080] Comparative Example 8 Gluing Method
[0081] The gluing was performed according to the method of Example 1, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-3 of the same weight portion, and the other conditions were the same as those of Example 1 to obtain a cured part.
[0082] Comparative Example 9 Gluing Method
[0083] The gluing was performed according to the method of Example 1, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-4 of the same weight portion, and the other conditions were the same as those of Example 1 to obtain a cured part.
[0084] Comparative Example 10 Gluing method
[0085] The gluing was performed according to the method of Example 1, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-5 of the same weight portion, and the other conditions were the same as those of Example 1 to obtain a cured part.
[0086] Application Example 1: Sealing method for the side of mobile terminal screen
[0087] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.2 mm is provided at the connection between the periphery of the screen and the shell.
[0088] S100. Glue dispensing: The epoxy adhesive BJ-1 is dispersed into small droplets under the action of an electric field with a voltage of 5000V (air pressure of 500kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 1mm / s to obtain a glued part;
[0089] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 2000mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0090] Application Example 2: Sealing Method for the Side of Mobile Terminal Screen
[0091] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.35 mm is provided at the connection between the periphery of the screen and the shell.
[0092] S100. Glue dispensing: The epoxy adhesive BJ-2 is dispersed into small droplets under the action of an electric field with a voltage of 3800V (air pressure of 350kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 2.5mm / s to obtain a glued part;
[0093] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 1500mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0094] Application Example 3: Sealing Method for the Side of Mobile Terminal Screen
[0095] The mobile terminal to be sealed includes a screen and a shell, and a gap with a width of 0.55 mm is provided at the connection between the periphery of the screen and the shell.
[0096] S100. Glue dispensing: The epoxy adhesive BJ-3 is dispersed into small droplets under the action of an electric field with a voltage of 2500V (air pressure of 200kPa) by using electrofluidic inkjet printing technology (Guangdong Sigu electrofluidic inkjet printer) and these small droplets are sprayed to the gap at a speed of 5mm / s to obtain a glued part;
[0097] S110. Irradiate UV light towards the gap of the dispensing part, and control the light intensity at 1800mJ / cm 2 , that is, the sealing is completed and the sealed part is obtained.
[0098] Comparative Application Example 1: Sealing Method for the Side of Mobile Terminal Screen
[0099] The glue sealing is performed according to the method of Application Example 4, except that piezoelectric spray valve technology is adopted and a Vermes piezoelectric spray valve is used for glue dispensing. Specifically, the equipment dispenses glue according to the following parameters: rise time 1.5msec, fall time 0.1msec, valve opening time 1.0msec, striker stroke 75%, delay 0.1msec, speed 55mm / s, air pressure 0.4MPa, nozzle diameter 0.10mm, and other conditions are the same as those in Application Example 4 to obtain a glue-sealed part.
[0100] Comparative Application Example 2: Sealing Method for the Side of Mobile Terminal Screen
[0101] The sealing is performed according to the method of Application Example 4, except that manual dispensing is used. The other conditions are the same as those of Application Example 4, and a sealed part is obtained.
[0102] Comparative Application Example 3: Sealing Method for the Side of Mobile Terminal Screen
[0103] The sealing is performed according to the method of Application Example 4, except that a robotic arm is used for dispensing glue. The other conditions are the same as those of Application Example 4, and a sealed glue part is obtained.
[0104] Comparative Application Example 4: Sealing Method for the Side of Mobile Terminal Screen
[0105] The glue sealing was performed according to the method of Application Example 4, except that the glue dispensing flow rate was controlled at 0.5 mm / s. The other conditions were the same as those of Application Example 4, and a glue-sealed part was obtained.
[0106] Comparative Application Example 5: Sealing Method for the Side of Mobile Terminal Screen
[0107] The glue sealing was performed according to the method of Application Example 4, except that the glue dispensing flow rate was controlled at 25 mm / s. The other conditions were the same as those of Application Example 4, and a glue-sealed part was obtained.
[0108] Comparative Application Example 6 Sealing Method for the Side of Mobile Terminal Screen
[0109] The sealing was performed according to the method of Application Example 4, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-1 of the same weight, and the other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0110] Comparative Application Example 7 Sealing Method for the Side of Mobile Terminal Screen
[0111] The sealing was performed according to the method of Application Example 4, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-2 of the same weight, and the other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0112] Comparative Application Example 8 Sealing Method for the Side of Mobile Terminal Screen
[0113] The sealing was performed according to the method of Application Example 4, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-3 of the same weight, and the other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0114] Comparative Application Example 9 Sealing Method for the Side of Mobile Terminal Screen
[0115] The sealing was performed according to the method of Application Example 4, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-4 of the same weight, and the other conditions were the same as those of Application Example 4 to obtain a sealed part.
[0116] Comparative Application Example 10 Sealing Method for the Side of Mobile Terminal Screen
[0117] The adhesive was applied according to the method of Application Example 4, except that the epoxy adhesive BJ-1 was replaced by the traditional adhesive DBJ-5 of the same weight. The other conditions were the same as those of Application Example 4 to obtain a sealed adhesive part.
[0118] Test Case
[0119] (1) Gluing accuracy: 5 parallel glue lines were drawn continuously and the glue line width was tested using an optical microscope. When the width ± deviation was ≤10 μm, the gluing accuracy was good. The results are shown in Table 1.
[0120] (2) Glue application stability: The equipment adopts dotting mode, and continuously applies dots 100 times. The diameter of the obtained glue dots is measured using an optical microscope. When the diameter ± deviation is ≥10μm, glue shortage and overflow will occur, and it is judged that the glue application is not continuous and stable. When the diameter ± deviation is ﹤10μm, it indicates that the glue application is continuous and stable. The results are shown in Table 1.
[0121] (3) Bonding strength: The cured articles obtained in the above examples and comparative examples were pulled apart in opposite directions using a universal testing machine, and the resulting shear force was the bonding strength. The results are shown in Table 1.
[0122] (4) Sweat resistance: Artificial sweat was dripped onto the adhesive overlap of the cured parts obtained in the above examples and comparative examples, and then wrapped with a dust-free cloth to achieve full wet contact, and then stored at room temperature (RT) for 72 hours, and then the bonding strength was tested according to the method of (3). The results are shown in Table 1.
[0123] (5) Grease resistance: Add a compound of edible oil, oleic acid and squalene in a volume ratio of 1:1:1 to the adhesive overlap of the cured sample obtained in (3), then wrap it with a dust-free cloth to achieve full wet contact, store it at room temperature (RT) for 24 hours, and then test the bonding strength according to the method in (3). The results are shown in Table 1.
[0124] (6) Sealing effect: The sealing effect of the sealed parts obtained in the above application examples and comparative application examples was observed. The obtained results are shown in Table 1.
[0125] Table 1
[0126]
[0127] It can be seen from the results in Table 1 that by using the method provided by the present invention for gluing, not only the gluing accuracy can be controlled within 10 μm, which indicates that the gluing accuracy is good, but also the gluing process can be continuously and stably operated. At the same time, when the glue layer is thin, it still has good bonding strength, and after being infiltrated and contacted with sweat and grease, the bonding strength can still be maintained at a high level, that is, the sweat and grease resistance are excellent.
[0128] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A sizing method, characterized in that: The method comprises dispersing the epoxy adhesive into small droplets under the action of an electric field and spraying the small droplets to the bonding site at a flow rate of 0.5 to 10 mm / s to complete the dispensing, wherein the voltage of the electric field acting on the epoxy adhesive is 2200 to 5000 V and the air pressure is 200 to 700 kPa, and then light curing is performed on the obtained dispensing part; the viscosity of the epoxy adhesive at 25°C is 5000 to 20000 cps and the thixotropy is 2 to 8, and the strength of the epoxy adhesive is 1000 mJ / cm 2 The bonding strength after UV light irradiation is 10 MPa or more.
2. The sizing method according to claim 1, characterized in that: The epoxy adhesive contains the following components in parts by weight:
3. The sizing method according to claim 2, characterized in that: The epoxy resin is an aromatic epoxy resin and / or an aliphatic epoxy resin; The cationic photoinitiator is a sulfonium salt compound and / or an iodonium salt compound; The photosensitizer is selected from at least one of benzil dimethyl ketal, hydroxycyclohexyl phenyl ketone, 2,4-diethylthiazolone, hydroxydimethyl acetophenone, methyl-(4-methylthiophenyl)-2-morpholinyl-acetone, 2,4-diethylthioxanthone, ethyl 4-dimethylaminobenzoate, benzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate; The toughening agent is selected from at least one of 1,4-butanediol, 1,6-hexanediol, polymethanol, polyethylene glycol, polypropylene glycol, glycerol, trihydroxy polyoxypropylene ether, D-glucose polyethylene oxide, polyoxyethylene polyoxypropylene ether, polymer of methyl ethylene oxide, ethylene oxide and 1,2,3-propanetriol, polymer of methyl ethylene oxide, 1,2-ethylenediamine and ethylene oxide, polymer of 1,2-ethylenediamine propylene oxide, trimethylol propane poly (oxypropylene) triether, polymer of methyl ethylene oxide, ethylene oxide ether and 2-ethyl-2-hydroxymethyl-1,3-propanediol, pentaerythritol propoxylate, polytetrahydrofuran diol, 1,1-[1-methylethyl)-bis-4,1-phenyleneoxy]-di-2-propanol, hydroxy-terminated polybutadiene, polyhexanediol adipate and polyethylene adipate; The silane coupling agent is selected from at least one of γ-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane, γ-glycidyloxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane and 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane; The inorganic filler is selected from at least one of silicon dioxide, fumed silica, aluminum oxide, talc, calcium carbonate, barium sulfate, mica, quartz powder, glass powder, aluminum hydroxide, zinc oxide, aluminum nitride, silicon carbide, silicon nitride, boron nitride, titanium nitride, dolomite, titanium dioxide, aluminum silicate, calcium silicate, bentonite, magnesium oxide, magnesium hydroxide, magnesium silicate, cobalt silicate, zirconium oxide and barium titanate; The color powder is selected from at least one of carbon black, red iron oxide, black iron oxide, titanium dioxide, brown iron oxide, permanent yellow SD-GTL PY14 and phthalocyanine blue.
4. The sizing method according to any one of claims 1 to 3, characterized in that: The spraying distance of the epoxy adhesive to the bonding site is 0.01 to 0.8 cm.
5. The sizing method according to any one of claims 1 to 3, characterized in that: The dispensing thickness of the epoxy adhesive is 0.03-0.5 mm.
6. The sizing method according to any one of claims 1 to 3, characterized in that: The intensity of the light curing is 1000-10000 mJ / cm 2 .
7. A method for sealing the side of a mobile terminal screen, wherein the mobile terminal comprises a screen and a housing, and a gap is provided at the connection between the periphery of the screen and the housing, characterized in that: The method comprises applying glue to the gap by using the method described in any one of claims 1 to 6.
8. The method for sealing the side edge of a mobile terminal screen according to claim 7, characterized in that: The width of the gap is 0.05-2 mm.
9. The method for sealing the side edge of a mobile terminal screen according to claim 7, characterized in that: The mobile terminal is a mobile phone or a computer.